The Influence of Islamic Moral Values on the Students’ Behavior in Aceh (Dinamika Ilmu, 2017)
This study shows the influence and relationship of Islamic moral values to the students’ behavior in Aceh Province. Learning Objects are the moral values of Islam achieved in learning in high school and vocational institutions that are assumed to affect the students’ behavior. The quantitative methods used in this study and was running by SPSS program. Data analysis using MRPI Likert Scale instrument. The data were taken from the students in the school totaling of 191 samples. The t-test and r test are used to analyze data from this research sample. The study found that Islamic moral values significantly correlated with the behavioral student at the level; [r (98) = 2.186 P